Defining the ferroptotic phenotype of beta cells in type 1 diabetes and its inhibition as a potential antidiabetic strategy - Markelic, Milica; Stancic, Ana; Saksida, Tamara; Grigorov, Ilijana; Micanovic, Dragica; Velickovic, Ksenija; Martinovic, Vesna; Savic, Nevena; Gudelj, Andjelija; Otasevic, Vesna (Frontiers in Endocrinology, 2023)
Recently, the involvement of ferroptotic cell death in the reduction of β-cell mass in diabetes has been demonstrated. To elucidate the mechanisms of β-cell ferroptosis and potential antidiabetic effects of the ferroptosis inhibitor ferrostatin-1 (Fer-1) in vivo, a mouse model of type 1 diabetes (T1D) was used. Animals were divided into three groups: control (vehicle-treated), diabetic (streptozotocin-treated, 40 mg/kg, from days 1-5), and diabetic treated with Fer-1 (1 mg/kg, from days 1-21). On day 22, glycemia and insulinemia wereas measured and pancreases were isolated for microscopic analyses. Diabetes disturbed general parameters of β-cell mass (islet size, β-cell abundance and distribution) and health (insulin and PDX-1 expression), increased lipid peroxidation in islet cells, and phagocytic removal of iron-containing material. It also downregulated the main players of the antiferroptotic pathway -Nrf2, GPX4, and xCT. In contrast, Fer-1 ameliorated the signs of deterioration of β-cells/islets, decreased lipid peroxidation, and reduced phagocytic activity, while upregulated expression of Nrf2 (and its nuclear translocation), GPX4, and xCT in β-cells/islets. Overall, our study confirms ferroptosis as an important mode of β-cell death in T1D and suggests antiferroptotic agents as a promising strategy for the prevention and treatment of diabetes.